Hydrogen Addition Influence for the Efficient and Ecological Parameters of Heavy-Duty Natural Gas Si Engine. (2017) - Korsakas, Vidas; Melaika, Mindaugas; Pukalskas, Saugirdas; Stravinskas, Paulius
Abstract: The paper presents the experimental research results of heavy-duty vehicle (public transport bus), fuelled with natural gas and hydrogen fuel mixtures. Spark ignition six cylinder engine tested with different hydrogen additions (from 5% up to 20% according to volume) in the natural gas fuel. The tests were performed on heavy-duty vehicle's dyno test stand in company "SG dujos Auto" research laboratory. The tests were carried out at three load points and one engine speed. Engine had originally a port fuel injection and exhaust gas recirculation system. Experiments showed that engine fuelled with hydrogen addition was able to achieve lower fuel consumption and brake specific fuel consumption. It was also possible to achieve small increase of engine efficiency. The exhaust gas measurements showed that hydrogen addition in natural gas reduced the CO, CO2 and HC emissions because of the H/C atom ratio change in fuel mixture and improved combustion process. The NOx emission level was decreasing, although bigger amounts of hydrogen were used in natural gas fuel.